Hot Vertical-Displacement-Event Process due to Internal Energy Perturbations for HL-2M Tokamak Plasma*Supported by the Chinese ITER Plan Project Foundation under Grant Nos 2013GB113001 and 2015GB105001, and the National Natural Science Foundation of China under Grant No 11575056. (May 2016) - Xue 薛, Lei 雷; Duan 段, Xu-Ru 旭如; Zheng 郑, Guo-Yao 国尧; Liu 刘, Yue-Qiang 钺强; Yan 晏, Shi-Lei 石磊; Dokuka, V. N.; Lukash, V. E.; Khayrutdinov, R. R.
Abstract : During the tokamak operation, variation of the stored energy can cause internal perturbations of the plasma. These perturbations may develop into large-scale vertical movement of the whole column for the vertically elongated tokamak, eventually generating the hot vertical displacement event (VDE). It will cause considerable damage to the machine. In this work, the hot VDE process due to stored energy perturbations is investigated by a mature non-linear time-evolution code DINA. The influence on the vertical instability, the displacement direction and the electromagnetic loads on in-vessel components during the hot VDE are analyzed. It is shown that a larger perturbation leads to faster development of the vertical instability. Meanwhile the variation of the Shafranov shift, due to the energy change, is related to the VDE direction. The vertical electromagnetic force on the vacuum vessel and the halo current flowing in the divertor baffle become larger in the case of VDE moving towards the X point.